(3MGTjI Ydi TQM eNJUQ GdSYO GdJaJGRGfi aj GdeYGfi hGdHjGfs - (3GdLQHis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3Edi HGH GdaUd hGdaUd hdaXe NWQg YQa HYVge GdHdGZI HeYQaI GdaUd hGdhUd bhdg dCfg CNUQ s
(3BNQgG (B:s
(3aEfc EPG fXQJ Edi ahGJM GdShQ QCjJ efg GdHdGZI hGdfaS eG jbUQ Yfg cfg ef UaI GdYHGQI cGdJMejOGJ s
(3HgG fXGe GdJYbjHIs
(3HChdg Jedc HGSe GdSjO YeQ CfSi Hf eMeO OjH GdTgjQ HGHf GdUbYGf GdHjQhJis
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
Keywords: (3GdHdGZIs